Folate-Receptor Positive Circulating Tumor Cell Is a Potential Diagnostic Marker of Prostate Cancer - Lian, Shenyi; Yang, Lujing; Feng, Qin; Wang, Ping; Wang, Yue; Li, Zhongwu (Frontiers in Oncology, 2021)
Folate-receptor positive circulating tumor cells (FR+CTCs) shows an important role in the diagnosis and dynamic monitoring for many solid tumors, however the application of FR+CTCs in prostate cancer remains unclear. We explored the potential application of FR+CTCs in this retrospective study. The levels of FR+CTCs were detected in 30 prostate cancer patients and 7 bladder cancer patients in Peking University Cancer Hospital from August 2017 to August 2021. Clinical and pathology data were collected. One-way ANOVA was used to compare the difference of FR+CTCs levels in patients with prostate cancer, bladder cancer and benign disease. The area under the receiver operating curve (AUROC) was used to compare the accuracy of FR+CTCs and tPSA in the diagnosis of prostate cancer. We found that levels of FR+CTCs were significantly higher in cancer patients (both prostate cancer and bladder cancer) than in patients with benign urinary disease (p < 0.001). Besides, FR+CTCs level was consistently high in the prostate cancer patients with different tPSA levels (p < 0.001), and it was significantly higher in the patients with f/tPSA levels< 0.16 than in those patients with f/tPSA levels> 0.16 (12.20±1.31 VS 8.73±0.92 FU/3mL, p = 0.043). The diagnosis efficiency of FR+CTCs is better than the tPSA in prostate cancer patients with tPSA<10ng/mL (0.871VS 0.857). In the prostate cancer patients with tPSA<10ng/mL and f/tPSA<0.16, combination of FR+CTCs and tPSA (AUROC 0.934) further increased diagnosis efficiency of each of these biomarkers alone (FR+CTCs: 0.912, tPSA:0.857). Therefore, FR+CTCs could serve as an early diagnosis marker in the prostate cancer patients with uncertain tPSA levels.